PENDIDIKAN ROHANI DALAM AL-QURAN - TARMIZI Tarmizi (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
Spiritual education is an education to teach the spiritual aspect human to improve their relationship with Allah through the worship and humble and obedient to Him and submit to His manhaj. The spiritual aspect is the soft elements with the existence as the main requirement for the biological processes associated with consciousness, the mind and the will; encompassing the soul, mind, heart, and lust. Spiritual education is done through Dzikrullah, Prayer, Fasting, Tazkiyah, Muraqabah, and Ridha.